The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1002/ange.19881000205
|View full text |Cite
|
Sign up to set email alerts
|

Zeolithe: Katalysatoren für die Synthese organischer Verbindungen

Abstract: Professor Helmut Dorfel zum 60. Gehurtstag gewidmetZeolithe als Katalysatoren haben sich in der Petrochemie und Mineralolverarbeitung groBtechnisch bewahrt. Die Zeolitheigenschaften wie Aciditat, Formselektivitat und Temperaturstabilitat lassen sich auch fur gezielte, hochselektive Synthesen im Zwischenproduktund Feinchemikalienbereich nutzen. Dieses interessante Einsatzgebiet hat sich in den letzten Jahren stetig ausgeweitet. Der vorliegende Beitrag faBt die in der organischen Synthese iiblichen Reaktionstype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
4

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(24 citation statements)
references
References 127 publications
0
20
0
4
Order By: Relevance
“…Such a behaviour can result from steric or electronic characteristics. If steric reasons dominate one could describe it as shape selectivity as documented for micro porous materials like zeolites [20]. We concluded that the electronic situation at the metal centre caused by the Ap ligands is dominating the responsibility for such a behaviour since the selectivity is observed for 3/4a and b and not just for the significantly higher crowded zirconium moieties (Fig.…”
Section: Olefin Polymerization and Formation Of Aluminum Aminopyridinmentioning
confidence: 91%
See 1 more Smart Citation
“…Such a behaviour can result from steric or electronic characteristics. If steric reasons dominate one could describe it as shape selectivity as documented for micro porous materials like zeolites [20]. We concluded that the electronic situation at the metal centre caused by the Ap ligands is dominating the responsibility for such a behaviour since the selectivity is observed for 3/4a and b and not just for the significantly higher crowded zirconium moieties (Fig.…”
Section: Olefin Polymerization and Formation Of Aluminum Aminopyridinmentioning
confidence: 91%
“…13 C NMR (63 MHz, C 6 D 6 , 298 K): d = 23. 4 (C 22,23 ), 24.4 (C 28,29,32,33 ), 24.8 (C 30,31 ), 26.6 (C 13,14 ), 31.0 (C 24,25,26,27 ), 34.9 (C 15 ), 55.3 (2 CH 3 ), 105.0 (C 3 ), 114.3 (C 5 ), 120.7 (C 9,11 ), 124.6 (C 18,20 ), 126.2 (C 19 ), 134.8 (C 4 ), 139.8 (C 7 ), 143.5 (C 8,12 ), 144.7 (C 17,21 ), 146.8 (C 10 ), 149.3 (C 16 ), 155.8 (C 6 ), 170.5 (C 2 ) ppm.…”
Section: Synthesis Of 4amentioning
confidence: 99%
“…Besonders bewährt haben sich mikroporöse anorganische Zeolithe. [366] Metallorganische Festkörper mit Zeolith-ähnlichen Eigenschaften zur Bindung von Gastmolekü-len sind in jüngster Zeit zwar zunehmend in das Blickfeld gerückt, ihre katalytischen Aktivitäten sind aber noch weitgehend unerforscht. [44,141,142,283,284,292,[367][368][369][370][371][372][373] Poröse Koordinationspolymere mit heterogen-katalytischen Aktivitäten sind in Tabelle 4 aufgeführt.…”
Section: Chemische Reaktionenunclassified
“…Several examples of shape-selective reactions can be found in a number of reviews. [17][18][19][20][21] Today the concept of "shape selectivity" is the basis for at least 17 commercial processes with annual hydrocarbon throughputs in more than 70 million metric tons year. [22] The widely accepted and applicable principles exploiting shape selectivity in molecular sieves are the following.…”
Section: Positioning Heterogeneous and Homogeneousmentioning
confidence: 99%